2008
DOI: 10.1016/j.cardfail.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nesiritide on Renal Function and Diuretic Responsiveness in Acutely Decompensated Heart Failure Patients With Renal Dysfunction

Abstract: When used as adjuvant "renal protective" therapy in patients with HF with renal dysfunction, the recommended dose of nesiritide reduced blood pressure, did not seem to worsen renal function, and suppressed endothelin but did not enhance diuretic responsiveness or prevent activation of the renin-angiotensin-aldosterone system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…In a preliminary study conduced in patients with HF and mild RI, Nesiritide did not improve renal function but rather showed a worsening respect to the baseline values at admission [37]. However, in a second recent report, Owan et al [38] did not reveal any renal function impairment in terms of creatinine levels and blood urea nitrogen in patients with acute HF. Now the ASCEND-HF is on going to better elucidate the hemodynamic efficacy and renal safety effect by its use [39].…”
mentioning
confidence: 87%
“…In a preliminary study conduced in patients with HF and mild RI, Nesiritide did not improve renal function but rather showed a worsening respect to the baseline values at admission [37]. However, in a second recent report, Owan et al [38] did not reveal any renal function impairment in terms of creatinine levels and blood urea nitrogen in patients with acute HF. Now the ASCEND-HF is on going to better elucidate the hemodynamic efficacy and renal safety effect by its use [39].…”
mentioning
confidence: 87%
“…Meanwhile the in-hospital death seemed to bear a little relation to the implementation of rhBNP. Several studies also indicated that rhBNP had fewer adverse effects and was safe in renal dysfunctional patients (13,17).…”
Section: Discussionmentioning
confidence: 99%
“…Patients in this study were admitted for treatment of volume overload but did not require intravenous vasodilator or inotropic therapy for the rapid relief of dyspnea. When used as an adjuvant therapy, the recommended dose of nesiritide induced a lesser increase in serum creatinine (p=0.048) and blood urea nitrogen (p=0.02) compared to the group that did not receive nesiritide [16]. In the Vasodilation in the Management of Acute Congestive heart failure (VMAC) trial, in patients with moderate or severe renal insufficiency and acutely decompensated congestive heart failure, nesiritide did not worsen renal function.…”
Section: Impact Of Nesiritide On Renal Functionmentioning
confidence: 98%